Off-Path TCP Exploit: How Wireless Routers Can Jeopardize Your Secrets - Chen, Weiteng; Qian, Zhiyun (27th USENIX Security Symposium (USENIX Security 18), 2018)
In this study, we discover a subtle yet serious timing side channel that exists in all generations of half-duplex IEEE 802.11 or Wi-Fi technology. Previous TCP injection attacks stem from software vulnerabilities which can be easily eliminated via software update, but the side channel we report is rooted in the fundamental design of IEEE 802.11 protocols. This design flaw means it is impossible to eliminate the side channel without substantial changes to the specification. By studying the TCP stacks of modern operating systems and their potential interactions with the side channel, we can construct reliable and practical off-path TCP injection attacks against the latest versions of all three major operating systems (macOS, Windows, and Linux). Our attack only requires a device connected to the Internet via a wireless router, and be reachable from an attack server (e.g., indirectly so by accessing to a malicious website). Among possible attacks scenarios, such as inferring the presence of connections and counting exchanged bytes, we demonstrate a particular threat where an off-path attacker can poison the web cache of an unsuspecting user within minutes (as fast as 30 seconds) under realistic network conditions.